Antibacterial effect of Caesalpinia spinosa (Tara) on mixed salivary flora - Huarino Acho, Mariella (2012)
The aim of this study was to determine the in vitro antibacterial effect of different concentrations of alcoholic extract of Caesalpinia spinosa “tara” (EACS) by disk diffusion method was used mixed salivary flora, to address them to the solutions of 6, 25, 12.5, 25, 50 and 75 mg/mL of EACS and positive controls compared with 0.12% chlorhexidine and alcohol 70 °. It was determined that the antibacterial effect of EACS on salivary mixed flora is more active in direct proportion to its concentration. Statistical analysis by Kruskal-Wallis test found significant differences at the level of 0,000 between different concentrations of the EACS, using the Mann - Whitney test, significant differences exist between the level of 0,000 and the positive control EACS Chlorhexidine Alcohol 0.12 % and 70 °. Furthermore EACS analysis by phytochemistry screening showed high presence of tannins, flavonoids, steroids, triterpenes and saponins. From the results it is concluded that the antibacterial effect has been demonstrated on mixed salivary flora.